Ultra-wideband and Polarization-Insensitive Perfect Absorber Using Multilayer Metamaterials, Lumped Resistors, and Strong Coupling Effects - Si-Jia Li; Peng-Xin Wu; He-Xiu Xu; Yu-Long Zhou; Xiang-Yu Cao; Jiang-Feng Han; Chen Zhang; Huan-Huan Yang; Zhao Zhang (Nanoscale Research Letters, 2018)
Abstract We theoretically and experimentally proposed a new structure of ultra-wideband and thin perfect metamaterial absorber loaded with lumped resistances. The thin absorber was composed of four dielectric layers, the metallic double split ring resonators (MDSRR) microstructures and a set of lumped resistors. The mechanism of the ultra-wideband absorption was analyzed and parametric study was also carried out to achieve ultra-wideband operation. The features of ultra-wideband, polarization-insensitivity, and angle-immune absorption were systematically characterized by the angular absorption spectrum, the near electric-field, the surface current distributions and dielectric and ohmic losses. Numerical results show that the proposed metamaterial absorber achieved perfect absorption with absorptivity larger than 80% at the normal incidences within 4.52~25.42 GHz (an absolute bandwidth of 20.9GHz), corresponding to a fractional bandwidth of 139.6%. For verification, a thin metamaterial absorber was implemented using the common printed circuit board method and then measured in a microwave anechoic chamber. Numerical and experimental results agreed well with each other and verified the desired polarization-insensitive ultra-wideband perfect absorption.